Utilization of Alocasia macrorrhiza Fermented Using Kombucha in Feed for the Growth of Asian Redtail Catfish (Hemibagrus nemurus) - Panuturi Julianto Siboro; Adelina Adelina; Indra Suharman (Jurnal Akuakultur SEBATIN, 2023)
The research was conducted at fish nutrition laboratory and the reservoir of the Faculty of Fisheries and Marine Science, University of Riau which was carried out from July to September 2021. This study aims to find out the effect of the use of sente leaf flour (Alocasia macrorrhiza) fermented with kombucha in feed on the growth of Asian Redtail Catfish (Hemibagrus nemurus). This study used a Completely Randomized Design (CRD) with 5 levels of treatment and 3 repetitions so that 15 experimental units were needed. Asian Redtail Catfish are used weigh 1.24 ± 0.02 g. The test fish used is inserted into the cage with a stocking solid of 25 heads / m3. The treatment used in this study is in the form of the use of fermented cente leaf flour in feed by 0, 5, 10, 15, 20%. Test feed is given as much as 10% of the biomass weight with the frequency of feeding 3 times a day, feeding is carried out for 56 days. To measure the digestibility of fish feed is given feed containing Cr2O3 as much as 0.5% of the amount of feed. Test fish measuring 1.24 ± 0.02 g are put into the aquarium with a stocking solid of 10 heads / cm3. After feeding, fish feces are collected and dried to measure their Cr2O3 and protein levels. The results showed sente leaf flour fermented using kombucha was able to replace soy flour by 20% in fish feed and gave the best results, namely feed digestibility 66.22%, protein digestibility 81.08%, feed efficiency 43.84%, protein retention 24.81%, specific growth rate 3.36% and 96.67% survival.